Immunisation schedule of the Spanish Association of Paediatrics: 2018 recommendations - David Moreno-Pérez; Francisco José Álvarez García; Javier Álvarez Aldeán; María José Cilleruelo Ortega; María Garcés Sánchez; Nuria García Sánchez; Ángel Hernández Merino; María Méndez Hernández; Manuel Merino Moína; Abián Montesdeoca Melián; Jesús Ruiz-Contreras (Elsevier, 2018)
The Advisory Committee on Vaccines of the Spanish Association of Paediatrics annually publishes the immunisation schedule considered optimal for children resident in Spain, according to available evidence on current vaccines.Regarding funded immunisations, 2 + 1 strategy (2, 4, 11-12 months) with hexavalent (DTPa-IPV-Hib-HB) and 13-valent pneumococcal vaccines are recommended.Administration of the 6-year booster dose with DTPa is recommended, and a poliomyelitis dose for children who had received the 2 + 1 scheme, as well as Tdap vaccine for adolescents and pregnant women in every pregnancy between 27 and 32 weeks' gestation.The two-dose scheme should be used for MMR (12 months and 2-4 years) and varicella (15 months and 2-4 years). MMRV vaccine could be applied as the second dose if available.Coverage of human papillomavirus vaccination in girls aged 12 with a two dose scheme (0, 6 months) should be improved. Information and recommendation for male adolescents about potential beneficial effects of this immunisation should be provided as well. The new 9 genotypes vaccine is now available, expanding the coverage for both gender. Regarding non-funded immunisations, Committee on Vaccines of the Spanish Association of Paediatrics recommends meningococcal B vaccination, with a 3 + 1 schedule, and requests to be included in the National Immunisation Program. Tetravalent meningococcal vaccine (MenACWY) is recommended to adolescents (14-18 years) who are going to live in countries with systematic vaccination against ACWY serogroups, and people >6 weeks of age with risk factors or travellers to countries with very high incidence.Vaccination against rotavirus is recommended in all infants. Resumen: El Comité Asesor de Vacunas de la Asociación Española de Pediatría publica anualmente el calendario de vacunaciones que estima idóneo para los niños residentes en España, teniendo en cuenta la evidencia disponible. En cuanto a las vacunas financiadas, se recomienda emplear el esquema 2+1 (2, 4 y 11-12 meses) con vacunas hexavalentes (DTPa-VPI-Hib-VHB) y con antineumocócica conjugada 13-valente. Se aconseja un refuerzo a los 6 años, preferentemente con DTPa, junto a una dosis de polio para aquellos que recibieron esquemas 2+1, así como vacunación con Tdpa en adolescentes y en cada embarazo, entre la 27 y 32 semanas. Se emplearán esquemas de dos dosis para triple vírica (12 meses y 2-4 años) y varicela (15 meses y 2-4 años). De haber disponibilidad, la segunda dosis se podría aplicar como vacuna tetravírica. Se deben incrementar las coberturas frente al papilomavirus en niñas de 12 años con dos dosis (0, 6 meses), así como informar y recomendar la vacunación de los varones, dados los beneficios potenciales de la misma. La nueva vacuna de 9 genotipos ya está disponible, ampliando la cobertura para ambos sexos. Respecto a vacunas no financiadas, se recomienda la antimeningocócica B, con esquema 3+1, solicitando su entrada en calendario. Se recomienda individualmente la vacuna antimeningocócica conjugada tetravalente (MenACWY) en adolescentes (14-18 años) que vayan a residir en países con vacunación sistemática frente a los serogrupos ACWY. También en mayores de 6 semanas de vida con factores de riesgo o viajeros a países de elevada incidencia.Es recomendable vacunar a todos los lactantes frente al rotavirus.